INTRODUCTION OF DIGITAL TECHNOLOGIES INTO THE EDUCATIONAL PROCESS IN UZBEKISTAN - Suleymanova Ramziya Marsilovna (European Journal of Humanities and Educational Advancements, 2024)
The article is devoted to the introduction of digital technologies into the education system at the present stage of social development. In particular, it is noted that digital technologies are aimed at improving the quality of education and training specialists who are guaranteed to be in demand in the labor market and who can easily and freely master mobile and Internet technologies. In the age of informatization and digitalization, the teacher himself must change and teach students to use digital technologies to obtain necessary and useful information, as well as to use these technologies. The modern education system is capable of providing society with a confident transition to the digital era, the benchmark for which is productivity growth, new types of work, and human needs. The ongoing informatization of education creates the basis for the transition to a new level.